BS EN ISO 10893-3 AMD2. Non-destructive testing of steel tubes. Part 3. Automated full peripheral flux leakage testing of seamless and welded (except submerged arc-welded) ferromagnetic steel tubes for the detection of longitudinal and/or transverse imperfections (2nd September 2019) - British Standards Institution,
No abstract available